Behavior Of Individual Orangutan Sumatera (Pongo Abelii) Before Direintroduction At The Orangutan Quarantine Station, Sibolangit, Deli Serdang, North Sumatera - Arlen Hanel John (Talenta Publisher, 2020)
The individual behavior of orangutan (Pongoabeli) before reintroduction to the wild was studied from March to June 2012 in orangutan quarantine station Batumbelin Sibolangit, Deli Serdang. The research used focal animal sampling method, at the same time the data recording was taken using instantenous method. The result showed that solitary behavior (39.34%) which was dominated by feeding (20.60%). The second highest (35.31%) was resting which was dominating by sitting (16.87%) followed by moving behavior (13.58%) which mostly was branching (7.54%). The least activity was competitive behavior (1.88%) which was dominated by streaking down each other (0.82%). The result also indicated an abnormal behavior among 3 orangutans observed such as eating their own feces.